Multiwavelength observations of the Galactic X-ray binaries IGR J20155+3827 and Swift J1713.4−4219. Issue 1 (5th February 2021) - Onori, F; Fiocchi, M; Masetti, N; Rojas, A F; Bazzano, A; Bassani, L; Bird, A J
ABSTRACT: In recent years, thanks to the continuous surveys performed by INTEGRAL and Swift satellites, our knowledge of the hard X-ray/soft gamma-ray sky has greatly improved. As a result it is now populated with about 2000 sources, both Galactic and extra-galactic, mainly discovered by IBIS and BAT instruments. Many different follow-up campaigns have been successfully performed by using a multiwavelength approach, shedding light on the nature of a number of these new hard X-ray sources. However, a fraction are still of an unidentified nature. This is mainly due to the lack of lower energy observations, which usually deliver a better constrained position for the sources, and the unavailability of the key observational properties, needed to obtain a proper physical characterization. Here, we report on the classification of two poorly studied Galactic X-ray transients IGR J20155+3827 and Swift J1713.4−4219, for which the combination of new and/or archival X-ray and optical/NIR (near-infrared) observations have allowed us to pinpoint their nature. In particular, thanks to XMM–Newton archival data together with new optical spectroscopic and archival optical/NIR photometric observations, we have been able to classify IGR J20155+3827 as a distant HMXB (high-mass X-ray binaries). The new INTEGRAL and Swift data collected during the 2019 X-ray outburst of Swift J1713.4−4219, in combination with the archival optical/NIR observations, suggest an LMXB (low-mass X-ray binaries) classification for this source.